Effects of pH, Temperature and Ionic Strength on Aggregation Behavior of Dodecyldiethoxylamine Oxide. Issue 2 (24th July 2013) - Wang, Ruitao; Li, Yunling; Song, Yongbo; Zhi, Lifei
Abstract: The isoelectric point of dodecyldiethoxylamine oxide (DDEAO) containing hydroxyethyl groups was determined with the method of acid–base titration. The isoelectric point value of DDEAO is 7.8. The effects of pH, temperature and ionic strength on the aggregation behavior of DDEAO were investigated by surface tension measurements. The results show a good surface activity over a large pH range, especially under weakly acidic conditions. The surface activity of DDEAO increases trend increasing temperature. The thermodynamic parameters were also evaluated and the results show that the micelle formation is entropy‐driven within the temperature range investigated. CMC values decrease with increases in ionic strength. The packing parameters ( P ) were evaluated and ensure the formation of vesicles for DDEAO at various pH values, which is expected to have potential applications in some fields, such as in nanomaterials synthesis and the application in drug delivery.